Analysis of Connectivity in Diffusion-Based Molecular Nano Communication Networks - Fereidouni, Arash (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: A nanonetwork is an interconnection of nano devices that are made up of nano-scale components. Several approaches for designing and implementing nanonetworks have been presented in recent years. Diffusion-based molecular communication is one of these approaches that use molecules as means of transmitting information in network. In diffusion-based molecular communication, molecules or particles diffuse in an aqueous environment under Fick’s laws of diffusion to move from transmitter to receiver. In order to have full cooperation among nano devices, there must exist a communication path between every communicating pair. Hence, the primary aim of this study is to employ methods used for analyzing random networks to evaluate connectivity properties of nanonetworks that employ diffusion-based molecular communication techniques. Extensive simulations have been performed to investigate the effects of varying node density, number of particles released per node, and concentration threshold for detection at the nodes. The corresponding results in two and three-dimensional environments have been presented. Keywords: Connectivity, diffusion, molecular communication, nanonetwork. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Nano-ağlar, nano-ölçekte bileşenleri olan nano-aygıtların birbiriyle bağlanmasıyla oluşur. Son yıllarda, nano-ağların tasarım ve oluşturulması için çeşitli yaklaşımlar önerilmiştir. Difüzyona dayalı moleküler iletişim, yani ağda bilginin moleküller kullanarak taşınması, bu yaklaşımlardan bir tanesidir. Difüzyona dayalı moleküler iletişimde moleküller sıvı ortamda Fick’in difuzyon kanunu ile vericiden alıcıya hareket eder. Nano-aygıtlar arasında tam işbirliği için her verici-alıcı çifti arasında bir iletişim yolunun olması gerekir. Dolayısıyla, bu çalışmanın esas amacı, rasgele ağların analizinde kullanılan metodları kullanarak difüzyona dayalı moleküler iletişim kullanan nano-ağların bağlantısallık özelliklerini analiz etmektir. Aygıt sıklığı, aygıt başına yayılan parçacık sayısı, aygıtların yoğunluk algılama eşiği değerlerinin bağlantısallıktaki etkilerini incelemek için simulasyonlar yapılmıştır. Hem iki hem de üç boyutlu ortamlarda elde edilen sonuçlar değerlendirilmiştir. Anahtar Kelimeler: Bağlantısallık, difüzyona, moleküler iletişim, nano-ağlar.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Assoc. Prof. Dr. Doğu Arifler.
Keywords: Computer Engineering; Computer Networks - Nanotechnology; Connectivity - Diffusion - Molecular Communication - Nanonetwork